THE EFFECT OF WORK EXPERIENCE, LOYALTY, AND MUTATION ON THE PERFORMANCE OF THE SECRETARIAT OF THE HOUSEHOLD REPRESENTATIVES (DPRK) BIREUEN DISTRICT: Zulfikar dan Azhari - Zulfikar; Azhari (LPPM-UNIKI, 2020)
The study was conducted on the staff of the Bireuen DPRK Secretariat, with the objectives being 1). Knowing the effect of work experience on employee performance, 2). Knowing the effect of loyalty on employee performance, 3). Knowing how the influence of mutations on employee performance, and 4). Knowing work experience, loyalty and mutation to the performance of the staff of the Bireuen Regency House of Representatives (DPRK). This research is in the form ofÂ uantitative research with a survey of 53 employees by collecting data through a questionnaire. And the method of data analysis with statistics with the path analysis approach. The results obtained that: a). There are direct and indirect effects of work experience, based on work loyalty and employee mutations on employee performance by 25.49 percent. b). There are direct and indirect effects of work loyalty, based on work experience and employee mutations on employee erformance by 24.22 percent. and c). There are direct and indirect effects of employee mutations based on work experience and work loyalty on employee performance by 27.78 percent. Based on the size of the coefficient of determination of 0.776 explains that the contribution of aspects of work experience, work loyalty and employeemutations to the performance of employees in the Secretariat of the DPRK Bireuen by 77.6%. While the rest (residual value) of the role of the variables not examined was 22.4%, showing that there are other factors that can affect performance variables, such as income, organizational climate, leadership, work facilities, and others.Â Keywords: Work Experience, Loyalty, Mutation, PerformanceÂ